Behavioral and EEGraphic Characterization of the Anticonvulsant Effects of the Predator Odor (TMT) in the Amygdala Rapid Kindling, a Model of Temporal Lobe Epilepsy - Delfino-Pereira, Polianna; Bertti-Dutra, Poliana; Del Vecchio, Flávio; de Oliveira, José A. Cortes; Medeiros, Daniel de Castro; Cestari, Daniel M.; Santos, Victor R.; Moraes, Marcio F. D.; Rosa, João L. G.; Mendes, Eduardo M. A. M.; Garcia-Cairasco, Norberto (Frontiers in Neurology, 2020)
BACKGROUND: Clinical and experimental evidence indicates that olfactory stimulation modulates limbic seizures, either blocking or inducing ictal activity. OBJECTIVE: Evaluate the behavioral and electroencephalographic (EEGraphic) effects of Dihydro-2,4,5-trimethylthiazoline (TMT) olfactory exposure on limbic seizures induced by Amygdala Rapid Kindling (ARK). MATERIAL AND METHODS: Wistar male rats (280-300 g) underwent stereotaxic surgery for electrodes implantation in Piriform Cortex (PC), Hippocampal Formation (HIP) and Amygdaloid Complex (AMYG). Part of the animals was exposed to a saturated chamber with water or TMT, while others had ARK and olfactory exposure prior to the 21st stimulus. Behavioral responses were measured by traditional seizure severity scales (Racine and Pinel & Rovner) and/or by sequential analysis/neuroethology. The electrographic activity of epileptogenic limbic networks was quantified by the occurrence of the first and second EEG afterdischarges, comparing the 1st and 21st stimulus. The spectral analysis (Fast Fourier Transform, FFT) of the first afterdischarge was performed at the 21st stimulus. RESULTS: TMT olfactory exposure reduced the seizure severity in kindled rats, altering the displayed behavioral sequence. Moreover, TMT decreased the occurrence of first and second afterdischarges, at the 21st stimulus, and altered the spectral features. CONCLUSIONS: Both behavioral and EEGraphic evaluations indicated that TMT, a potent molecule with strong biological relevance, in fact, "predator odor", suppressed the epileptiform activity in limbic networks.